A C@MoSe-2@CNT nanocomposite heterojunction material for sodium-ion battery anode
By constructing C@MoSe2@CNT nanocomposite heterojunction material, the problems of poor conductivity and material volume expansion are solved, high specific capacity and good cycle stability are achieved, and it is suitable for sodium ion battery negative electrode materials.
Patent Information
- Application Number
- CN202210476918.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-05-02
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2042-05-02
AI Technical Summary
The existing sodium ion battery negative electrode material MoSe2 has poor conductivity, and the material volume expands during the embedding/de-embedding of lithium ions, resulting in the active material being easily detached from the current collector, causing the battery capacity to decay sharply.
C@MoSe2@CNT nanocomposite heterojunction material is used to mix with carbon nanotubes through molybdenum-based complexes, selenized in situ to form MoSe2, and a carbon protective layer is formed through a carbonization process to construct a three-layer C/MoSe2/CNT nanostructure.
It improves the conductivity and cycling stability of MoSe2, enhances the storage capacity of sodium ions and battery capacity, and reduces the battery energy consumption and synthesis cycle.
Smart Images

Figure CN115377373B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a method for synthesizing a sodium ion battery negative electrode technical material, and in particular to a method for synthesizing a C@MoSe2@CNT nanocomposite heterojunction material used as a sodium ion battery negative electrode, belonging to the field of synthesis of sodium ion battery negative electrode technical materials. Background Art
[0002] Compared with lithium, sodium is abundant in the earth (2.36%) and widely distributed [SURVEY US G. Mineralcommodity summaries 2022[R]. Reston, VA, 2022.] and sodium-ion batteries have the same energy storage mechanism as lithium-ion batteries, making them an ideal choice to replace lithium-ion batteries. However, since the radius of sodium ions is much larger than that of lithium ions (Na + vs.Li + ), so the negative electrode materials of lithium ions are not suitable for direct use in sodium ion batteries, such as graphite, a commercial negative electrode material for lithium ions. [WANG BW, GAO X, XU LQ, et al. Advanced Carbon Materials for Sodium-Ion Capacitors[J]. Batteries&Supercaps, 2021, 4(4): 538-53.] Therefore, it is urgent to develop negative electrode materials suitable for sodium ion batteries.Conventional sodium negative electrode materials include transition metal oxides [LIU QN, HU Z, LI WJ, et al. Sodium transition metal oxides: the preferred cathode choice for future sodium-ion batteries? [J]. Energy & Environmental Science, 2021, 14 (1): 158-79.], alloy materials [WUY, YAO Y, WANG LF, et al. Recent Progress on Modification Strategies of Alloy-based Anode Materials for Alkali-ion Batteries [J]. Chemical Research in Chinese Universities, 2021, 37 (2): 200-9.], and transition metal chalcogenides [LIU Q, HU Z, LI W, et al. Sodium transition metal oxides: the preferred cathode choice for future sodium-ion batteries? [J]. Energy & Environmental Science, 2021, 14 (1): 158-79.], etc. Among them, transition metal chalcogenides have the advantages of high theoretical capacity, abundant earth reserves of elements, and low price, especially the two-dimensional material MoSe2, which has a special Se-Mo-Se sandwich layered structure, with the layers connected by covalent bonds and the layers attracted to each other by van der Waals forces, and has a similar structure to graphite [SU Q, CAO XX, YU T, et al. Binding MoSe2 with dual protection carbon for high-performance sodium storage [J]. Journal of Materials Chemistry A, 2019, 7 (40): 22871-8.]. Compared with graphite, MoSe2 has a larger interlayer spacing (about 0.65nm), which is very suitable for ion embedding and extraction, and is regarded as a very promising sodium storage material. However, as a semiconductor material, MoSe2 has poor conductivity, resulting in poor rate performance; at the same time, the volume of the material will expand during the insertion / deinsertion process of lithium ions, causing the active material MoSe2 to easily detach from the current collector, resulting in a sharp decay of the battery capacity.
[0003] To solve the above problems, reducing the size of MoSe2 and optimizing its morphology have been shown to be possible ways to achieve a short diffusion path for sodium ions. A common and effective method is: combining with carbon materials to prepare carbon@MoSe2, [TANG YC, ZHAO ZB, WANG YW, et al. Carbon-Stabilized Interlayer-Expanded Few-Layer MoSe2Nanosheets for Sodium Ion Batteries with Enhanced Rate Capability and CyclingPerformance[J].Acs Applied Materials&Interfaces,2016,8(47):32324-32.]MoSe2@carbon[LI B,LIU Y,LI Y,et al. Dual-Functional Template-Directed Synthesis ofMoSe2 / Carbon Hybrid Nanotubes with Highly Disordered Layer Structures asEfficient Alkali-Ion Storage Anodes beyond Lithium[J].Acs Applied Materials&Interfaces,2020,12(2):2390-9.] and C@MoSe2@carbon[YOUUSAF M,WANG Y,CHEN Y, et al. A 3D Trilayered CNT / MoSe2 / C Heterostructure with an Expanded MoSe2Interlayer Spacing for an Efficient Sodium Storage[J]. Advanced Energy Materials, 2019, 9(30).] The composite material improves the capacity and stability of SIBs. Guo first synthesized C@MoSe2@CNT three-layer heterojunction material to provide high specific capacity (484 mAh g -1 at 100mAg -1 ) and good cycle stability (after 500 cycles at 500mAg -1 Still 347mAhg -1The specific capacity of the MoSe2 electrode is 2.54kWh, while the carbon coating of the MoSe2 electrode can act as a barrier between the electrolyte and the active material to protect the active material. [YOUSAF M, WANG Y, CHEN Y, et al. A 3D Trilayered CNT / MoSe2 / C Heterostructure with an Expanded MoSe2 Interlayer Spacing for an Efficient Sodium Storage[J]. Advanced Energy Materials, 2019, 9(30).] The morphology of this 3D trilayered C / MoSe2 / CNT heterojunction material can be precisely controlled through multiple steps. Specifically, first, the MoSe2 layer can provide a uniform coating on the CNT template through a simple hydrothermal process, followed by an annealing process to produce an intermediate CNT / MoSe2 composite material; subsequently, glucose is used as a carbon source to uniformly coat the carbon layer on the CNT / MoSe2 composite material through a carbonization process. In this case, the highly porous (>99%) CNT framework material plays a key role in constructing the 3D trilayer structure. However, this highly porous (>99%) CNT framework is not easy to use as anode material for SIBs on a large scale, and the multiple synthesis steps have long synthesis cycles (about 3 days) and high energy consumption (high temperature calcination times). Therefore, it will be challenging to develop a simpler and more effective method and use commercially available CNTs to construct 3D three-layer C@MoSe2@CNT nanostructures for sodium ion batteries. However, commercially available carbon nanotubes are often entangled with each other and have no porous structure, making it difficult to load metal salts into three-layer materials.
[0004] As is well known, the characteristic structure of CNT allows them to interact with organic molecules through non-covalent forces, such as hydrogen bonding, π-π stacking and electrostatic forces, [CHEN W, DUAN L, ZHU D. Adsorption of polar and nonpolar organic chemicals to carbon nanotubes [J]. Environmental Science & Technology, 2007, 41 (24): 8295-300.] shows that CNT can be easily covalently or non-covalently hybridized and the organic units of the molybdenum-based complexes have the potential to be converted into carbon materials, while the metals of the molybdenum-based complexes have the potential to form metal-based materials. Therefore, we envision a simple and efficient method to construct a three-layer C@MoSe2@CNT composite material. First, the molybdenum-based complex is mixed with carbon nanotubes, and the molybdenum-based complex can be adsorbed on the surface of the carbon nanotubes, and then the precursor metal complex is converted into MoSe2 in situ by selenization treatment, and the organic matter of the molybdenum-based complex is used as a carbon source to form a carbon protective layer.
[0005] In this work, we have adopted a simple method to prepare trilayer C@MoSe2@CNT via in situ synthesis of MoSe2, as shown in Scheme 1, by the reaction of MoCl5 with ethylene glycol and / or poly(ethylene glycol) (PEG) to form Mo-based organometallic complexes. The Mo-based organometallic complexes are then hybridized with CNTs by ultrasonic treatment to form organic-inorganic hybrid materials. To further reveal the behavior of Mo@CNT-based composites, density functional theory (DFT) calculations using the Castep method were performed. Figure 1 The Mo@CNT based composite is shown. From the calculation results, the distance between the Mo composite and CNT is And the adsorption energy is -9.78eV, which means that the Mo-based composite will be easily adsorbed onto CNT. Afterwards, the Mo@CNT composite was transferred to a ceramic ark and the collected PEG-200-2-C@MoSe2@CNT was subjected to XRD ( Figure 1 a) Characterization shows that the product is a three-layer heterojunction structure. The excellent sodium storage performance exhibited by this structure can be attributed to the synergistic effect of the double carbon network and the enlarged interlayer spacing of MoSe2. When used as an anode material for SIBS, PEG-200-2-C@MoSe2@CNT can provide a high capacity of 1483mAhg at a current density of 0.1mA. -1 initial capacity and can still maintain 426mAh g after 500 cycles -1 Excellent capacity; at a high current density of 2A g -1After 3000 cycles, it can still maintain 206.3mAhg -1 Therefore, the research on constructing C@MoSe2@CNT negative electrode materials may provide a potential option for future rechargeable batteries. Summary of the invention
[0006] The purpose of the present invention is to solve the shortcomings of the prior art and to propose a C@MoSe2@CNT nanocomposite heterojunction material used as a negative electrode for a sodium ion battery.
[0007] In order to achieve the above object, the present invention adopts the following technical solutions:
[0008] A C@MoSe2@CNT nanocomposite heterojunction material used as a negative electrode of a sodium ion battery, wherein the preparation method of the composite material comprises the following steps:
[0009] S1, dissolving carbon nanotubes in ethylene glycol (polyethylene glycol), and then adding platinum pentachloride and an organic solvent to generate a platinum metal organic complex; the best effect is: polyethylene glycol is added to replace the amount of ethylene glycol, that is, the total amount of polyethylene glycol and ethylene glycol added is 15ml, in this example, 2ml polyethylene glycol 200 and 13ml ethylene glycol are added (the product obtained after firing is named PEG-200-2-C@MoSe2@CNT), Mo and polyethylene glycol form a platinum-based metal organic complex, and finally selenium is added;
[0010] S2, ultrasonically treating the solution to promote uniform dispersion of CNTs and uniformly adsorb the molybdenum metal organic complex on the surface of CNTs, thus forming a molybdenum metal organic complex@CNT composite;
[0011] S3, taking out the above solution and placing it in a ceramic ark, and then transferring it to a tubular furnace containing Ar atmosphere for calcination at a heating rate of 4-6°C / Min;
[0012] S4. After ultrasonic and calcination reactions, the Mo element in the precursor dispersion is in situ selenized into MoSe2, and the organic components are in situ converted into carbon materials, ultimately generating C@MoSe2@CNT nanocomposite heterojunction materials.
[0013] Preferably, in S1, the polyethylene glycol is not limited to polyethylene glycol-200, and the solvent ratio of polyethylene glycol-200 to ethylene glycol is 0.1 to 0.6.
[0014] Preferably, in S1, the temperature during the adding process is 20-30°C.
[0015] Preferably, in S1, the concentration of molybdenum pentachloride is 0.08-0.12 mmol mL -1 .
[0016] Preferably, in S1, the concentration of selenium is 0.2-0.4 mmol mL -1 .
[0017] Preferably, in S1, the molar ratio of selenium to molybdenum pentachloride is 1.5 to 3:1.
[0018] Preferably, in S1, the concentration of CNT is 0.3-0.7 mg mL -1 .
[0019] Preferably, in S2, ultrasound is applied for 2 to 4 hours to enhance the CNT dispersion effect.
[0020] Preferably, in S3, the protective atmosphere used is argon, which is maintained at 60-100°C for 3-5 hours, then heated to 130-300°C and maintained for 3-5 hours, and finally heated to a calcination temperature of 500-1300°C for 4-6 hours.
[0021] Preferably, in S4: the composite material is a product of a C@MoSe2@CNT nano three-layer composite heterojunction material (a three-layer heterojunction structure formed by the growth of MoSe2 around CNT and the coating of carbon on the surface of MoSe2); the coating thickness of the outermost layer of the composite material with 2 ml of polyethylene glycol-200 significantly changed, which was thinner than that of the material without polyethylene glycol-200, and the battery capacity was significantly increased to 600 mAhg -1 .
[0022] Compared with the prior art, the technical solution of the present invention has the following beneficial technical effects:
[0023] The present invention uses molybdenum pentachloride, Se, CNT, and ethylene glycol (polyethylene glycol) as raw materials, and synthesizes C@MoSe2@CNT nanocomposite heterojunction materials by ultrasonic dispersion and subsequent calcination. Compared with similar products, the product obtained by this method is simple, has low energy consumption, high repeatability, high dispersibility of MoSe2 and CNT, few layers, and good cycle stability, which is conducive to its industrial production. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 (a) X-ray powder diffraction, (b) (c) Raman of C@MoSe2, C@MoSe2@CNT, and PEG-200-2-C@MoSe2@CNT nanocomposite heterojunction materials proposed in the present invention, and (d) (e) (f) XPS spectra of PEG-200-2-C@MoSe2@CNT nanocomposite heterojunction materials;
[0025] Figure 2Thermogravimetric graphs of C@MoSe2, C@MoSe2@CNT(a), and PEG-200-2-C@MoSe2@CNT nanocomposite heterojunction materials proposed in the present invention;
[0026] Figure 3 (a), (b) scanning electron microscope images, (c), (d) transmission electron microscope images of the C@MoSe2 nanocomposite heterojunction material proposed in the present invention;
[0027] Figure 4 Scanning electron microscope images of the nanocomposite heterojunction materials C@MoSe2@CNT (a), PEG-200-2-C@MoSe2@CNT (b), and PEG-200-5-C@MoSe2@CNT (c) proposed in the present invention;
[0028] Figure 5 (a) SEM image and (b), (c), (d), (e) TEM images of the C@MoSe2@CNT nanocomposite heterojunction material proposed in the present invention; (f) SEM image and (g), (h), (i), (j) TEM images of the PEG-200-2-C@MoSe2@CNT nanocomposite heterojunction material;
[0029] Figure 6 (a) Cyclic voltammogram of the PEG200-2-C@MoSe2@CNT nanocomposite heterojunction material proposed in the present invention, (b) Charge and discharge capacity voltage diagram of the PEG200-2-C@MoSe2@CN nanocomposite heterojunction material, (c) C@MoSe2, C@MoSe2@CNT, PEG200-2-C@MoSe2@CNT and PEG200-5-C@MoSe2@CNT batteries at 0.1Ag -1 (d) PEG200-2-C@MoSe2@CNT battery charge and discharge rate performance diagram, (e) PEG200-2-C@MoSe2@CNT battery at 2Ag -1 Long cycle high current charge and discharge test under current density;
[0030] Figure 7 The migration energy of Na atoms in MoSe2 and MoSe2 / CNT. (a), (b) Schematic diagram of the migration of Na atoms in MoSe2 / CNT and MoSe2. (e), (f) The migration energy in the two systems. Obviously, the migration energy of Na atoms in MoSe2 / CNT (1.78 eV) is lower than that in MoSe2 (2.45 eV). DETAILED DESCRIPTION
[0031] In order to make the above-mentioned features, advantages and purposes of the present invention more clear and easy to understand, the content of the present invention is further described in detail below in conjunction with specific embodiments. Many specific details are set forth in the above description to facilitate a full understanding of the present invention. However, the present invention can be implemented in many other ways different from those described herein, and those skilled in the art can make similar improvements without violating the connotation of the present invention, so the present invention is not limited by the specific implementation disclosed below.
[0032] The reaction raw materials and catalysts involved in the following examples, unless otherwise specified, are conventional commercially available reagents on the market.
[0033] The technical solutions in the embodiments of the present invention will be described clearly and completely below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments.
[0034] In Example 1, a C@MoSe2 nanocomposite heterojunction material used as a negative electrode of a sodium ion battery, and a method for preparing the composite material comprises the following steps:
[0035] S1, take 27.2 mg of molybdenum pentachloride and dissolve it in 15 mL of ethylene glycol to generate a molybdenum-based metal organic complex, and dissolve 24 mg of Se in the above solution;
[0036] S2, ultrasonicate the solution for 4 hours to evenly disperse the molybdenum-based metal organic complex and Se.
[0037] S3, taking out the above solution and putting it into a ceramic ark, then transferring it to a tube furnace containing Ar atmosphere and calcining it at 80°C, 180°C, and 800°C for 4h, 4h, and 4h, with a heating rate of 5°C@Min;
[0038] S4. After ultrasonic and calcination reactions, the Mo element in the precursor dispersion is in situ selenized into MoSe2, and the organic components are in situ converted into carbon materials, ultimately generating C@MoSe2 nanocomposite heterojunction materials.
[0039] 2. Further, the C@MoSe2 nanocomposite heterojunction material used as the negative electrode of a sodium ion battery according to the above requirements is characterized in that, in S1, the temperature during the addition process is room temperature, i.e., 20 to 30°C.
[0040] 3. Further, a C@MoSe2 nanocomposite heterojunction material used as a negative electrode of a sodium ion battery according to the above requirements is characterized in that the composite material is a product of a C@MoSe2 nanocomposite heterojunction structure in which carbon is coated on the surface of MoSe2, and MoSe2 is a few-layer structure.
[0041] 4. Further, the obtained C@MoSe2 nanocomposite heterojunction material was mixed with acetylene black and sodium alginate in a mass ratio of (8:1:1), ground and dispersed in a mixed solvent of water and ethanol, and then evenly coated on a copper foil as a working electrode.
[0042] In Example 2, a C@MoSe2@CNT nanocomposite heterojunction material used as a negative electrode of a sodium ion battery, the preparation method of the composite material comprises the following steps:
[0043] S1, take 27.2 mg of molybdenum pentachloride and dissolve it in 15 mL of ethylene glycol to generate a molybdenum metal organic complex, then add 24 mg of Se and 8 mg of CNT and dissolve them in the above solution;
[0044] S2. Ultrasonicate the solution for 4 hours to evenly disperse Se and CNT, and at the same time, evenly adsorb the molybdenum-based metal organic complex on the surface of CNT, thus forming a molybdenum-based metal organic complex@CNT composite.
[0045] S3, taking out the above solution and putting it into a ceramic ark, then transferring it to a tube furnace containing Ar atmosphere and calcining it at 80°C, 180°C, and 800°C for 4h, 4h, and 4h, with a heating rate of 5°C@Min;
[0046] S4. After ultrasonic and calcination reactions, the Mo element in the precursor dispersion is in situ selenized into MoSe2, and the organic components are in situ converted into carbon materials, ultimately generating C@MoSe2@CNT nanocomposite heterojunction materials.
[0047] 2. Further, a C@MoSe2@CNT nanocomposite heterojunction material for use as a negative electrode of a sodium ion battery according to the above requirements is characterized in that in S1, the temperature during the addition process is room temperature, i.e., 20 to 30°C;.
[0048] 3. Further, a C@MoSe2@CNT nanocomposite heterojunction material for use as a negative electrode of a sodium ion battery according to the above requirements is characterized in that the composite material is a product of a C@MoSe2@CNT nano three-layer composite heterojunction material, that is, a three-layer heterojunction structure in which MoSe2 grows around CNT and carbon is coated on the surface of MoSe2.
[0049] 4. Further, the obtained C@MoSe2@CNT nano three-layer composite heterojunction material was mixed with acetylene black and sodium alginate in a mass ratio of 8:1:1, ground and dispersed in water and ethanol, and then evenly coated on copper foil as a working electrode.
[0050] In Example 3, a PEG-200-2-C@MoSe2@CNT nanocomposite heterojunction material used as a negative electrode of a sodium ion battery, the preparation method of the composite material comprises the following steps:
[0051] S1. Weigh 8 mg of carbon nanotubes and dissolve them in a mixed solvent of 13 mL of ethylene glycol and 2 mL of polyethylene glycol. Then add 27.2 mg of molybdenum pentachloride and organic solvent to form a molybdenum metal organic complex. Mo and polyethylene glycol form a molybdenum-based metal organic complex. Finally, add 24 mg of Se
[0052] S2. Ultrasonicate the solution for 4 hours to evenly disperse Se and CNTs, and at the same time, evenly adsorb the molybdenum-based metal organic complex on the surface of CNTs, thus forming a molybdenum-based metal organic complex@CNT composite.
[0053] S3, taking out the above solution and putting it into a porcelain ark, then transferring it to a tube furnace containing Ar atmosphere and calcining it at 80°C, 180°C, and 800°C for 4h, 4h, and 4h, respectively, with a heating rate of 5°C@Min;
[0054] S4. After ultrasonic and calcination reactions, the Mo element in the precursor dispersion is in situ selenized to MoSe2, and the organic component is in situ converted into carbon material, finally generating PEG-200-2-C@MoSe2@CNT nanocomposite heterojunction material.
[0055] 2. A PEG-200-2-C@MoSe2@CNT nanocomposite heterojunction material used as a negative electrode of a sodium ion battery according to the above requirements is characterized in that, in S1, the polyethylene glycol in this example is polyethylene glycol-200.
[0056] 3. A PEG-200-2-C@MoSe2@CNT nanocomposite heterojunction material used as a negative electrode of a sodium ion battery according to the above requirements, characterized in that, in S1, the temperature during the addition process is room temperature, i.e., 20 to 30°C;.
[0057] 4. A PEG-200-2-C@MoSe2@CNT nanocomposite heterojunction material used as a negative electrode of a sodium ion battery according to the above requirements, characterized in that: the composite material is a product of a C@MoSe2@CNT nano three-layer composite heterojunction material (a three-layer heterojunction structure formed by the growth of MoSe2 around CNT and the coating of carbon on the surface of MoSe2); the coating thickness of the outermost layer of the composite material with 2 ml of polyethylene glycol-200 is significantly changed, which is thinner than that of the material without polyethylene glycol-200, and the battery capacity is significantly increased to 600 mAh g -1
[0058] 5. Further, the obtained PEG-200-2-C@MoSe2@CNT nano three-layer composite heterojunction material was mixed with acetylene black and sodium alginate in a mass ratio of 8:1:1, ground and dispersed in water and ethanol, and then evenly coated on copper foil as a working electrode.
[0059] The following examples 1-3 are used as representatives for characterization:
[0060] SEM and TEM images of C@MoSe2@CNT and PEG200-2-C@MoSe2@CNT samples are shown in Figure 2. Figure 5 As shown. Figure 5 a, 5b and 5c are respectively Figure 5 By comparing 5f, 5g and 5h, it can be inferred that PEG-200 disperses carbon nanotubes and molybdenum-based metal complexes better than ethylene glycol, which helps to improve the utilization of active materials. HRTEM image of PEG200-2-C@MoSe2@CNT ( Figure 5 i) shows that the edges of the MoSe2 nanosheets are at an angle to the CNTs and are completely surrounded by a thin layer of carbon, whereas in C@MoSe2@CNT, the MoSe2 nanosheets grow parallel to the CNTs and are completely surrounded by a thick carbon layer ( Figure 5 d). Figure 5 h and Figure 5 i shows that it is precisely this thicker carbon coating that takes over the contact between the edge of MoSe2 and the carbon nanotube. This is mainly because the carbon chain of PEG-200 is longer than that of ethylene glycol, and the formed molybdenum-based complex is more easily adsorbed on CNTs and provides more carbon sources in the process of in-situ carbon formation between MoSe2 and CNTs; and the raised edge of MoSe2 is conducive to the generation of more contact sites between MoSe2 and the electrolyte, thereby shortening the migration distance of Na+. Figure S1d, Figure 5 e and Figure 5 The HRTEM images in j show that the interlayer distance of MoSe2 in C@MoSe2, C@MoSe2@CNT and PEG-200-2-C@MoSe2@CNT composites is about 0.65nm, which corresponds to the (002) plane. Figure 5 It can be clearly seen in Figures 5e and 5j that the MoSe2 layer is sandwiched between the CNT and carbon layers, and the interlayer distance of the MoSe2(002) plane is changed from C@MoSe2@CNT( Figure 5 e) increased from ≈0.65 to ≈0.68 nm to PEG-200-2 C@MoSe2@CNT ( Figure 5 j) from ≈0.66 to ≈0.68 nm; the increase in interlayer spacing not only improves the ion storage capacity of the composite material, but also improves the inherent conductivity of the composite material. At the same time, PEG-200-2-C@MoSe2@CNT( Figure 5 j) The carbon coating in C@MoSe2@CNT( Figure 5e) is thinner, which means that the active material of the former is more accessible to the electrolyte and its battery performance will be better. By analyzing the SEM and TEM images of C@MoSe2@CNT and PEG200-2-C@MoSe2@CNT samples, it can be seen that: compared with ethylene glycol, PEG-200 has a strong effect on the morphology of MoSe2, which will be more conducive to improving the battery performance of MoSe2 as a negative electrode material for SIBs.
[0061] Figure 1 a shows that the peak at 27.3° in the XRD spectra of samples C@MoSe2, C@MoSe2@CNT and PEG-200-2-C@MoSe2@CNT is related to carbon, while the other peaks correspond to the hexagonal phase of MoSe2 (JCPDS 29–0914) with a space group of P63 / mmc, which confirms the high purity of the products. In the Raman spectrum, it can be clearly observed that the D peak and G peak of carbon nanotubes in C@MoSe2, C@MoSe2@CNT and PEG-200-2-C@MoSe2@CNT are 1352cm-1 and 1586cm-1, respectively ( Figure 1 b). As well as the out-of-plane vibration (A1g) at 239.34 cm-1, there is a vibration corresponding to the in-plane atomic vibration (E2g1) at 283.6 cm-1 ( Figure 1 c). The atomic vibration is due to the vibration of two adjacent rigid layers of MoSe2, which confirms the layered structure of the grown MoSe2. It was observed that the intensity ratio of A1g to E2g1 of C@MoSe2 and C@MoSe2@CNT was almost the same, which confirmed that the carbon coating did not adversely affect the MoSe2 layered structure. However, the decrease in the A1g intensity of PEG200-2-C@MoSe2@CNT compared with C@MoSe2 and C@MoSe2@CNT was very obvious, confirming that the introduction of PEG carbon coating had an adverse effect on the MoSe2 layered structure. Compared with the A1g and E2g1 peaks of C@MoSe2@CNT and PEG200-2-C@MoSe2@CNT, C@MoSe2 showed a significant red shift, which was due to the increase in the interlayer distance.
[0062] XPS spectroscopy was used to analyze the surface chemical composition and oxidation state of the elements in the PEG200-2-C@MoSe2@CNT composite. Figure 1 d) clearly shows the Mo, Se, and C signals, and the smaller O1s signal indicates that the product is of high purity. In the Mo 3d spectrum, the two peaks at 229.03 eV and 232.19 eV correspond to Mo 3d5 / 2 and 3d3 / 2, respectively, indicating the Mo+4 state ( Figure 1e); The weak peak at 230.4 eV corresponds to Se 3s. In the Se 3d spectrum, the Se 3d peaks at 54.51 eV (Se 3d5 / 2) and 55.39 eV (Se 3d3 / 2) correspond to the peaks of the Se+2 state ( Figure 1 e). The broad peak at 55.8 eV in the Se 3d spectrum is related to the intermediate fitting line attributed to the oxidation state of Se ( Figure 1 e). The ratio of MoSe2 in MoSe2@C, MoSe2@C@CNT and PEG-200-2-C@MoSe2@CNT was determined by thermogravimetric analysis (TGA). Figure 2 When heated in air, MoSe2 oxidizes to form MoO3 and SeO2, so the mass increases before 350°C ( Figure 2 ). After that, there are two stages of mass loss: the first stage is due to the sublimation of SeO2, and the second is due to the oxidation by carbon. According to the TGA results, the MoSe2 ratio is 70.74% in MoSe2@C, while in MoSe2@C@CNT and PEG-200-2-C@MoSe2@CNT, it is 57.06% and 49.86%, respectively.
[0063] The PEG-200-2-C@MoSe2@CNT composites were used as anodes for battery testing to evaluate the Na+ storage performance in the battery. The electrochemical performance of the composites was evaluated by cyclic voltammetry (CV) measurements, scanning the voltage range of 0.01–3.00 V at 0.3 mV s-1 for the initial four cycles during the first cathode / discharge process ( Figure 5 a), three peaks of 1.2, 0.67 and 0.42 V appear; the first cathode or reduction peak is at 1.2 V, which is related to the insertion of Na+ into the MoSe2 layer to form NaxMoSe2; the second is 0.68 V, which is caused by the irreversible decomposition of the electrolyte due to the formation of a stable and thin NaF-like solid electrolyte interface (SEI) layer caused by the addition of fluoroethylene carbonate (FEC); in the cathode process, the main cathode peaks observed are at about 0.6 V and 0.3 V, which are mainly attributed to the decomposition of MoSe2 into metallic Mo and Na2Se caused by Na+ insertion. During the first anode / charging process of PEG-200-2-C@MoSe2@CNT, a peak of 1.69 V can be observed, which is due to the partial oxidation of Mo to MoSe2 and the partial conversion of Na2Se to Se and polyselenide intermediates. From the second cycle, the shapes of the C@MoSe2@CNT curves begin to overlap, showing a high degree of electrochemical reversibility and stability. Figure 5 b shows the current at 100 mA g -1, constant current discharge / charge voltage distribution curve of PEG-200-2-C@MoSe2@CNT in the range of 0.01 to 3.00 V; and the first discharge and charge capacities of PEG-200-2-C@MoSe2@CNT are 1483 mAh g -1 and 710 mAhg -1 , while the decrease in the first charge capacity can be attributed to the irreversible electrolyte degradation and the formation of the SEI film as mentioned above.
[0064] In order to further investigate the effect of the carbon layer on the sodiumation / de-sodiumation, the current density of 100 mA g -1 The cycling behaviors of C@MoSe2, C@MoSe2@CNT, PEG-200-2-C@MoSe2@CNT and PEG-200-5-C@MoSe2@CNT carbon nanotube composites under Figure 5 c). After the 10th cycle, the C@MoSe2@CNT, PEG-200-2-C@MoSe2@CNT, and PEG-200-5-C@MoSe2@CNT hybrids have high electrochemical reversibility and stability. The capacity of PEG200-2-C@MoSe2@CNT increases from 600 mAh g at the 20th cycle to 1.5 mAh g at the 20th cycle. -1 Down to 556 mAh g at the 300th cycle -1 The capacities of C@MoSe2@CNT and PEG-200-5-C@MoSe2@CNT are relatively low, and the capacities also decrease with the increase of cycle number, but the decrease is smaller than that of PEG-200-2-C@MoSe2@CNT ( Figure 5 c). Because the carbon coating of C@MoSe2@CNT is thicker than that of PEG-200-2-C@MoSe2@CNT, Na + The ions must diffuse into the outer amorphous carbon shell before reaching the active material (MoSe2). + Ions may diffuse into MoSe2 through vacancies or defects in the amorphous carbon shell rather than following an intercalation mechanism. Therefore, the slow diffusion through thick carbon layers, compared with thinner carbon coatings, has an adverse effect on the overall process. Without the participation of CNTs, the C@MoSe2 electrode dropped from 680 mAh g at the 20th cycle to 1.5 mAh g at 2.5 Å. -1 83 mAh g at the 300th cycle -1 , showing a huge capacity decay ( Figure 5c). This means that when used as a sodium ion anode, the C@MoSe2@CNT core and the selection of a suitable thickness of the carbon layer are crucial to improving the capacity and stability of the CNT. The PEG-200-2-C@MoSe2@CNT material has a good performance at current densities of 100, 200, 400, 600, 800, 1000, 1400, 1600, 2000, 2400 and 3000 mAg -1 568, 491, 472, 467, 451, 439, 423, 417, 404, 399 and 392 mAh g -1 The discharge capacity of the battery is very impressive with impressive rate performance; when the current density is restored to 100, 200 and 400 mAg -1 It recovered 574, 514 and 499 mAh g -1 The discharge capacity ( Figure 5 d). For the long-cycle test, the PEG-200-2-C@MoSe2@CNT hybrid exhibits a good capacity retention (90%) with a specific capacity of 212 mAh g after 1000 to 3000 cycles. -1 However, in the 20th cycle, the capacity retention rate of C@MoSe2 is only 30% ( Figure 5 e). Compared with C@MoSe2, the enhanced Na+ storage performance of PEG-200-2-C@MoSe2@CNT is due to the substantial increase in the interlayer spacing of MoSe2 after carbon coating, as it provides superior insertion channels and sites for sodium storage. In addition, the raised edges of MoSe2 are conducive to the contact between MoSe2 and the electrolyte, improving the utilization of active materials, thereby shortening the migration distance of sodium ions and improving the storage capacity of the battery.
[0065] In summary, we demonstrated a simple method to prepare three-layer C / MoSe2 / CNT nanostructures by in situ synthesis of MoSe2 using Mo-based organic complexes. First, a layer of Mo-based organic complex was controlled to grow on the surface of CNTs, followed by in situ selenization of Mo to MoSe2; then, both MoSe2 and CNTs were confined in conductive porous carbon by direct and stepwise carbonization using the outer organic complex layer as a carbon source at different temperatures. When used as an electrode, the optimized C / MoSe2 / CNT material provided a high specific capacity (684 mAh g -1 At 100 mAg -1 ) and good cycle stability (554 mAh g after 300 cycles -1 The capacity of 206.3 mAh g after 3000 cycles -1 At the same time, DFT calculation results show that ( Figure 7), the hybridization of MoSe2 and carbon nanotubes can effectively reduce the Na + Diffusion barrier (2.45eV to 1.78eV), increasing the Na + Reversibility of storage.
[0066] In Examples 1-3, the metal organic complex precursor components of the present invention are determined, highly repeatable, and simple in process. After ultrasonic dispersion and calcination reaction, the Mo element is selenized in situ to MoSe2, and the organic component is converted into graphitized carbon (C) in situ to form an outer layer C-coated MoSe2 structure, which can effectively alleviate the volume change of MoSe2 during the charge and discharge process and improve the cycle life. In addition, the MoSe2 particles in the samples obtained by the present invention are small, the number of layers is small, and the distribution is uniform, which is conducive to exposing active sites and improving reversible capacity. The presence of CNT is conducive to improving conductivity, thereby improving high current performance and improving the conductivity of the material.
[0067] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.
Claims
1. A C@MoSe2@CNT nanocomposite heterojunction material used as a negative electrode of a sodium ion battery, wherein the preparation method of the composite material comprises the following steps: S1, dissolving carbon nanotubes in ethylene glycol, then adding platinum pentachloride and organic solvent to generate platinum metal organic complex; the best effect is: polyethylene glycol is added to replace the amount of ethylene glycol, that is, the total amount of polyethylene glycol and ethylene glycol added is 15ml, in this example, 2ml polyethylene glycol 200 and 13ml ethylene glycol are added, Mo and polyethylene glycol form a platinum-based metal organic complex, and finally selenium is added; S2, ultrasonically treating the solution to promote uniform dispersion of CNTs and uniformly adsorb the molybdenum metal organic complex on the surface of CNTs, thus forming a molybdenum metal organic complex@CNT composite; S3, taking out the above solution and putting it into a ceramic ark, and then transferring it to a tubular furnace containing Ar atmosphere for calcination at a heating rate of 4-6°C / Min; S4. After ultrasonic and calcination reactions, the Mo element in the precursor dispersion is in situ selenized into MoSe2, and the organic components are in situ converted into carbon materials, ultimately generating C@MoSe2@CNT nanocomposite heterojunction materials.
2. The C@MoSe2@CNT nanocomposite heterojunction material used as a negative electrode for a sodium ion battery according to claim 1, characterized in that In S1, the polyethylene glycol is not limited to polyethylene glycol-200, and the solvent ratio of polyethylene glycol-200 to ethylene glycol is 0.1 to 0.
6.
3. The MoSe2@CNT microsphere composite material used as a negative electrode of a sodium ion battery according to claim 1, characterized in that In S1, the temperature during the adding process is 20-30°C.
4. The MoSe2@CNT microsphere composite material used as a negative electrode of a sodium ion battery according to claim 1, characterized in that In S1, the concentration of molybdenum pentachloride is 0.08-0.12 mmol mL -1 .
5. The MoSe2@CNT microsphere composite material used as a negative electrode of a sodium ion battery according to claim 1, characterized in that In the S1, the concentration of selenium is 0.2-0.4 mmol mL -1 .
6. The MoSe2@CNT microsphere composite material used as a negative electrode of a sodium ion battery according to claim 1, characterized in that In the S1, the molar ratio of selenium to molybdenum pentachloride is 1.5 to 3:
1.
7. The C@MoSe2@CNT nanocomposite heterojunction material used as a negative electrode for a sodium ion battery according to claim 1, characterized in that In S1, the concentration of CNT is 0.3-0.7 mg mL -1 .
8. The C@MoSe2@CNT nanocomposite heterojunction material used as a negative electrode for a sodium ion battery according to claim 1, characterized in that In S2, ultrasound was applied for 2 to 4 h to enhance the CNT dispersion effect.
9. The C@MoSe2@CNT nanocomposite heterojunction material used as a negative electrode for a sodium ion battery according to claim 1, characterized in that In S3, the protective atmosphere used is argon, which is maintained at 60-100°C for 3-5 hours, then heated to 130-300°C and maintained for 3-5 hours, and finally heated to a calcination temperature of 500-1300°C, and the calcination time is 4-6 hours.
Citation Information
Patent Citations
Molybdenum selenide based composite cathode material for sodium-ion battery and preparation method thereof
CN105006570A
Nitrogen-doped porous carbon ball / manganic manganous oxide nanometer composite electrode material and preparation method thereof
CN105355874A